CULTURAL IDENTITY AND SYMBOLIC INTERACTIONISM IN KARMA BROWN’S NOVEL “RECIPE FOR A PERFECT WIFE”: ANTHROPOLOGY OF LITERATURE STUDY - Widyastuti, Divya; Juliansyah, Juliansyah; Afiyati, Alia (Lembaga Penelitian dan Pendidikan Mandala, 2022)
In a literary work, two characters can be narrated as the attention center that contains the cultural identity from certain generation. Meanwhile, a symbol actually can cause an interaction within characters. This research discusses about cultural identity and symbolic interactionism reflected in a novel. There is a novel entitled “Recipe for a Perfect Wife” by Karma Brown that tells about two female characters that are represented as a housewife from different generation. This research uses descriptive qualitative as the research methodology and content analysis as the method in analyzing the object of the research, a novel entitled “Recipe for a Perfect Wife”. This research also uses the intrinsic approach to analyze the characterization, plot, and setting. This research reveals two kinds of a housewife. They are a housewife and working woman, and a full-housewife. This research finds five cultural identities in the past and present time that is related with a housewife reflected by two female characters in the novel by using cultural identity theory by Stuart Hall. This research also reveals the symbol and memory even three concepts of symbolic interactionism that is mind, self, and society based on symbolic interactionism theory by George Herbert Mead.